IMPLEMENTASI MODEL PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 KELAS II SDN 101749 KLUMPANG KEBUN KAB. DELI SERDANG - Vinny Nurindah Sari; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2023)
The purpose of this study, namely 1) To find out how to implement the bold learning model. 2) To find out what factors are the obstacles in the implementation of bold learning, and 3) To find out the supporting factors in the brave learning process during the pandemic 4) To determine the teacher's ability to design bold learning media during the covid-19 pandemic in class II SDN 101749 Klumpang Kebun Academic Year 2021 This research is a qualitative research with descriptive analysis technique. Analysis of research data obtained from the process of searching and compiling systematically, data obtained from observations, interviews and the field, namely data collection, data reduction, data presentation, conclusions and levers. The results showed that, 1) The implementation of the bold learning model in class II was by utilizing several applications, using one sheet of lesson plans and evaluating worksheets that could be taken and collected directly to school. 2) The inhibiting factors in the implementation of courage learning are the lack of effectiveness and time efficiency, the lack of enthusiasm of students and the lack of students' understanding of the material. 3) Supporting factors for bold learning, namely, schools facilitate wifi for teachers in schools, and students are given free internet quota. 4) The teacher designs learning by making learning videos and sending them through the WhatsApp application so that students can reopen the learning materials provided by the teacher and re-learn them.